A Homemade Smart Phone Microscope for Single-Particle Fluorescence Microscopy - Varra, Travis; Simpson, Amy; Roesler, Benton; Nilsson, Zach; Ryan, Duncan; Van Erdewyk, Michael; Schuttlefield Christus, Jennifer D; Sambur, Justin B (Journal of chemical education, 2020)
Imaging tools advance nanoscience education by enabling students to see and engage with matter that is not visible to the human eye. However, undergraduate students generally lack access to expensive research-grade electron and optical microscopes, especially at primarily undergraduate institutions. New, inexpensive, and hands-on microscopy activities are needed to advance nanoscience education. Here we demonstrate a microscopy activity in which students assemble a total internal reflection-based fluorescence microscope using interlocking building bricks and image a series of micrometer- and nanometer-sized fluorescent beads. The hands-on experiments are accompanied by fluorescence image analysis, single-particle detection, and particle size measurements. The activity enables students to explore the optical diffraction limit effect that was the subject of the 2014 Nobel Prize in Chemistry. This activity introduces undergraduate students to underlying principles of optical microscopy, optical components and light sources, Snell’s law, and image processing and analysis procedures while reinforcing major concepts like data analysis and statistics, fluorescence, emission, and absorption.